Employee training and development - Noe, Raymond A. (New York, NY McGrawHill Education, 2023)
"Traditionally, training and development were not viewed as activities that could help companies create "value" and successfully deal with competitive challenges. Today, that view has changed. Companies that use innovative training and development practices are likely to report better financial performance than their competitors that do not. Training and development also help a company develop the human capital needed to meet competitive challenges"--
Includes bibliographical references and index.
Keywords: Employees -- Training of